A randomised controlled trial of digital breast tomosynthesis vs digital mammography as primary screening tests: Screening results over subsequent episodes of the Proteus Donna study. Issue 10 (30th June 2022) - Armaroli, Paola; Frigerio, Alfonso; Correale, Loredana; Ponti, Antonio; Artuso, Franca; Casella, Denise; Falco, Paolo; Favettini, Elisabetta; Fonio, Paolo; Giordano, Livia; Marra, Vincenzo; Milanesio, Luisella; et al.
Abstract: Proteus Donna is a randomised controlled trial aimed at prospectively evaluating screening with digital breast tomosynthesis (DBT), including interval cancer detection (ICD) and cancer detection (CD) in the analysis as a cumulative measure over subsequent screening episodes. Consenting women aged 46 to 68 attending the regional Breast Screening Service were randomly assigned to conventional digital mammography (DM, control arm) or DBT in addition to DM (DBT, study arm). At the subsequent round all participants underwent DM. Thirty‐six months follow‐up allowed for the identification of cancers detected in the subsequent screening and interscreening interval. Relative risk (RR) and 95% confidence interval (95% CI) were computed. Cumulative CD and Nelson‐Aalen incidence were analysed over the follow‐up period. Between 31 December 2014 and 31 December 2017, 43 022 women were randomised to DM and 30 844 to DBT. At baseline, CD was significantly higher (RR: 1.44, 95% CI: 1.21‐1.71) in the study arm. ICD did not differ significantly between the two arms (RR: 0.92, 95% CI: 0.62‐1.35). At subsequent screening with DM, the CD was lower (nearly significant) in the study arm (RR: 0.83, 95% CI: 0.65‐1.06). Over the follow‐up period, the cumulative CD (comprehensive of ICD) was slightly higher in the study arm (RR: 1.15, 95% CI: 1.01‐1.31). The Nelson‐Aalen cumulative incidence over time remained significantly higher in the study arm for approximately 24 months. Benign lesions detection was higher in the study arm at baseline and lower at subsequent tests. Outcomes are consistent with a lead time gain of DBT compared to DM, with an increase in false positives and moderate overdiagnosis. What's new?: Digital breast tomosynthesis (DBT), involving three‐dimensional visual reconstruction of the breast using low‐dose mammography, is a promising advance in breast cancer screening. Higher cancer detection (CD) for DBT compared to digital mammography (DM) has been demonstrated. Little is known, however, about the relationship between DBT, interval cancer detection, CD at subsequent screening and overdiagnosis. Our study describes the results of Proteus Donna, a randomized controlled trial aimed at prospectively evaluating breast cancer screening with DBT compared to DM. Analyses show that, at baseline DBT was associated with a significant increase in recall for further evaluation, and CD, while at subsequent screening with DM, CD was lower in the DBT arm. ICD detection was similar for DBT and DM. Outcomes are consistent with a lead time gain of DBT compared with DM, with an increase of false positive and moderate overdiagnosis.